Police Authority in Enforcing the Professional Code of Ethics Against Members of The National Police Who Commit Criminal Acts - Azhari; Saiful Asmi Hasibuan (International Journal of Society and Law, 2024)
The Regulation of the Chief of the National Police of the Republic of Indonesia Number 14 of 2011 defines the Professional Code of Ethics for police officers, outlining norms for behavior and duties to ensure proper law enforcement, public order, and security. Despite this, there are significant challenges in maintaining ethical standards within the National Police, including instances of human rights violations, abuse of power, and other misconduct. Law Number 2 of 2002 describes the police's role in maintaining security and order, but violations by officers highlight issues in internal discipline and ethical enforcement. The Propam Division is responsible for overseeing police ethics and discipline. However, the enforcement process involves complex procedures, with disciplinary actions and criminal penalties often handled separately. Recommendations for sanctions come from the Police Code of Ethics Commission but are not always binding. This study, titled "Police Authority in Enforcement of the Professional Code of Ethics Against Members of the National Police who Commit Criminal Acts," explores the effectiveness of ethical enforcement and internal supervision within the police force. It emphasizes the need for stringent disciplinary measures and innovative practices to uphold professionalism and reduce violations, ensuring more effective law enforcement and greater public trust..